WS2/Si3N4-Based Biosensor for Low-Concentration Coronavirus Detection - Talia Tene; Fabian Arias Arias; Karina I. Paredes-Páliz; Ana M. Cunachi Pillajo; Ana Gabriela Flores Huilcapi; Luis Santiago Carrera Almendariz; Stefano Bellucci (Micromachines)
This study presents the optimization of two SPR biosensors, Sys3 and Sys5, for SARS-CoV-2 detection at concentrations of 0.01–100 nM. Sys3, with a 55 nm silver layer, a 13 nm silicon nitride layer, and a 10 nm ssDNA layer, achieved a figure of merit (FoM) of 571.24 RIU−1, a signal-to-noise ratio (SNR) of 0.12, and a detection accuracy (DA) of 48.93 × 10−2. Sys5, incorporating a 50 nm silver layer, a 10 nm silicon nitride layer, a 10 nm ssDNA layer, and a 1.6 nm tungsten disulfide layer (L = 2), demonstrated a higher sensitivity of 305.33 °/RIU and a lower limit of detection (LoD) of 1.65 × 10−5. Sys3 outshined in precision with low attenuation (<1%), while Sys5 provided enhanced sensitivity and lower detection limits, crucial for early-stage viral detection. These configurations align with the refractive index ranges of clinical SARS-CoV-2 samples, showcasing their diagnostic potential. Future work will focus on experimental validation and integration into point-of-care platforms.